The number of torsion divisors in a strongly F-regular ring is bounded by the reciprocal of F-signature. Issue 4 (3rd April 2022) - Martin, I.
Abstract: Polstra showed that the cardinality of the torsion subgroup of the divisor class group of a local strongly F -regular ring is finite. We expand upon this result and prove that the reciprocal of the F -signature of a local strongly F -regular ring R bounds the cardinality of the torsion subgroup of the divisor class group of R .